2014
DOI: 10.5489/cuaj.1448
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone deficiency syndrome and cardiovascular health: An assessment of beliefs, knowledge and practice of general practitioners and cardiologists in Victoria, BC

Abstract: Introduction: Testosterone deficiency syndrome (TDS) has been shown to be an independent cardiovascular risk factor and a predisposing factor for metabolic syndrome. As general practitioners and cardiologists primarily care for these patients, we sought to assess their knowledge, beliefs and practice patterns with respect to TDS and cardiac health. Methods: We distributed a questionnaire to all 20 cardiologists and a cohort of 128 family practitioners in Victoria, British Columbia. Of the 13 questions, 10 asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In the present analysis, we demonstrated that even when failure to account for immortal‐time bias did not qualitatively change the study conclusions (as in, from benefit to harm), it may qualitatively change the study findings in such a way to significantly influence practice. As there is considerable debate regarding the risk–benefit balance of TRT , changes in risk estimates of ≥10% may be of importance in patient counselling and decision making.…”
Section: Discussionmentioning
confidence: 99%
“…In the present analysis, we demonstrated that even when failure to account for immortal‐time bias did not qualitatively change the study conclusions (as in, from benefit to harm), it may qualitatively change the study findings in such a way to significantly influence practice. As there is considerable debate regarding the risk–benefit balance of TRT , changes in risk estimates of ≥10% may be of importance in patient counselling and decision making.…”
Section: Discussionmentioning
confidence: 99%
“…1 Although the questionnaire used is not shown and there is no evidence that it was validated, the responders appear to be adequately informed and properly cautious on the management of a condition which is at the centre of considerable and, frequently poorly informed controversy. The controversy is bolstered by the "expert" views from all of walks of life: from endocrinologists and epidemiologists to urological surgeons and gerontologists, from the lay press to the regulatory agencies and from the pharmaceutical to the film industries.…”
mentioning
confidence: 99%